High liver fibrosis scores in metabolic dysfunction-associated fatty liver disease patients are associated with adverse atrial remodeling and atrial fibrillation recurrence following catheter ablation - Decoin, Raphaël; Butruille, Laura; Defrancq, Thomas; Robert, Jordan; Destrait, Nicolas; Coisne, Augustin; Aghezzaf, Samy; Woitrain, Eloise; Gouda, Zouriatou; Schino, Sofia; Klein, Cédric; Maboudou, Patrice; et al. (Frontiers in Endocrinology, 2022)
Background: A number of epidemiological studies have suggested an association between Metabolic-dysfunction Associated Fatty Liver Disease (MAFLD) and the incidence of atrial fibrillation (AF). However, the pathogenesis leading to AF in the context of MAFLD remains unclear. We therefore aimed at assessing the impact of MAFLD and liver fibrosis status on left atrium (LA) structure and function. Methods: Patients with a Fatty Liver Index (FLI) >60 and the presence of metabolic comorbidities were classified MAFLD+ . In MAFLD+ patients, liver fibrosis severity was defined using the NAFLD Fibrosis Score (NFS) as follows: MAFLD w/o fibrosis (NFS≦-1.455); MAFLD w/ indeterminate fibrosis (-1.455